2022
DOI: 10.47162/rjme.63.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Laryngeal malignancies – epidemiological data and particularities of the cases diagnosed in Western Romania (October 2016–July 2020)

Abstract: In the last decade, the incidence and mortality associated with laryngeal malignancies has experienced an unfavorable evolution in Romania, in terms of this pathology the country that has become the leader, among the European Union (EU)-27 countries. The aim of the present retrospective study was to analyze the epidemiological data regarding laryngeal cancer and histopathological (HP) particularities in patients diagnosed in Western Romania. Within three years and 10 months (during October 2016-July 2020) in E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Locally advanced cancers, including T3-4 and N1-3 disease, are more difficult to treat and usually require combination therapies. Although these cancers are not candidates for laryngeal preservation surgery if surgically resectable, definitive radiation therapy in association with cisplatin chemotherapy remains an option to organ preservation surgery [ 14 ]. According to Dyckhoff et al [ 15 ], in advanced laryngeal cancer, organ preservation with primary conservative treatment is likely to result in a significantly worse outcome in terms of overall survival, and the patients should be informed about this.…”
Section: Discussionmentioning
confidence: 99%
“…Locally advanced cancers, including T3-4 and N1-3 disease, are more difficult to treat and usually require combination therapies. Although these cancers are not candidates for laryngeal preservation surgery if surgically resectable, definitive radiation therapy in association with cisplatin chemotherapy remains an option to organ preservation surgery [ 14 ]. According to Dyckhoff et al [ 15 ], in advanced laryngeal cancer, organ preservation with primary conservative treatment is likely to result in a significantly worse outcome in terms of overall survival, and the patients should be informed about this.…”
Section: Discussionmentioning
confidence: 99%
“…Oropharyngeal cancer (OPC) is a malignancy that affects the oral cavity and pharyngeal region [ 1 ]. In recent decades, research has revealed a significant association between human papillomavirus (HPV) infection and the development of oropharyngeal cancer [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sendo assim, os casos de tuberculose pulmonar são divididos em primários e secundários. A tuberculose primária, responsável por cerca de 5-10% dos casos, se desenvolve logo após a infecção; já a tuberculose secundária (90-95% dos casos), é decorrente da reativação do bacilo que já estava presente no pulmão, porém de forma controlada, ou latente (NITU et al, 2017). O espalhamento do bacilo pelo pulmão pode levar à pneumonia lobular obstrutiva, e pode se desenvolver para pneumonia caseosa, caracterizada pelas lesões típicas da tuberculose e fibrose, que podem comprometer toda a fisiologia do órgão (HUNTER, 2018).…”
Section: Lista De Siglasunclassified